Evaluation of mass attenuation coefficient of concrete sample for different traits (Brazilian Journal of Radiation Sciences (BJRS), 2022)
Concrete is widely used in the world and is the main material for civil construction. Due to its properties, it has different uses such as structural, filling and shielding. The aim of this work is to compare experimental and theoretical mass attenuation coefficient for concrete with different traits and determine the one with the best performance. For this, density, X-ray diffraction, mass attenuation coefficient (experimental with a Cs137 source, simulated by MCNP and theoretical determined with XCOM platform) and compressive strength were determined for three different traits of cement mortar (standardized sand, conventional sand and artificial sand). The X-ray diffraction showed more compounds for artificial sand’s samples. Density showed no significant variation. The samples showed a good agreement for experimental, simulated and theoretical mass attenuation coefficient. Standardized sand’s samples had the best performance for mechanical test, with a compressive strength 47.4% higher than artificial sand’s samples and 38.2% higher than conventional sand’s samples. It is possible to conclude that, since mass attenuation coefficient showed no significant difference, standardized sand’s samples is more indicated to be used for shielding than the others.